Syllable Priming With Pseudowords in the Lexical Decision Task. - Mathey, Stphanie; Doignon-Camus, Nadge; Chetail, Fabienne (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2013)
This study investigated the processes underlying the effect of masked syllable priming in French with pseudoword primes and word targets. Two lexical-decision task (LDT) experiments examined whether the syllable priming effect depends on syllable frequency and might rely on a general abstract structure. The results of Experiment 1 revealed an inhibitory priming effect, with pseudoword primes and word targets sharing a high-frequency first syllable, which was not due to the abstract syllable structure. In contrast, no inhibition was observed with a low-frequency first syllable in Experiment 2. Syllable frequency appears to be an important factor determining the speed of target processing in masked priming. This is attributed to variations in the respective contributions of sublexical activation and lexical inhibition processes.